Evaluating the Emergence of Winning Tickets by Structured Pruning of Convolutional Networks - Magalhães, Whendell F.; Ferreira, Jeferson; Gomes, Herman M.; Marinho, Leandro B.; Silveira, Plínio (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
The recently introduced Lottery Ticket Hypothesis has created a new investigation front in neural network pruning. The hypothesis states that it is possible to find subnetworks with high generalization capabilities (winning tickets) from an over-parameterized neural network. One step of the algorithm implementing the hypothesis requires resetting the weights of the pruned network to their initial random values. More recent variations of this step may involve: (i) resetting the weights to the values they had at an early epoch of the unpruned network training, or (ii) keeping the final training weights and resetting only the learning rate schedule. Despite some studies have investigated the above variations, mostly with unstructured pruning, we do not know of existing evaluations focusing on structured pruning regarding local and global pruning variations. In this context, this paper presents novel empirical evidence that it is possible to obtain winning tickets when performing structured pruning of convolutional neural networks. We setup an experiment using the VGG-16 network trained on the CIFAR-10 dataset and compared networks (pruned at different compression levels) got by weight rewinding and learning rate rewinding methods, under local and global pruning regimes. We use the unpruned network as baseline and also compare the resulting pruned networks with their versions trained with randomly initialized weights. Overall, local pruning failed to find winning tickets for both rewinding methods. When using global pruning, weight rewinding produced a few winning tickets (limited to low pruning levels only) and performed nearly the same or worse compared to random initialization. Learning rate rewinding, under global pruning, produced the best results, since it has found winning tickets at most pruning levels and outperformed the baseline.